The Efficiency of Extensive Reading Using Reading A-Z On Vocabulary Enrichment (Conference on English Language Teaching, 2023)
Gadgets can either distract or facilitate students' learning activities in this digital age. As for positive impact, gadgets are effective tools to intrigue students' perceptions and behaviors in reading. Reading A-Z, one of the digital literacy platforms with more than 2000 fiction and nonfiction books at various levels, has been encouraging its users worldwide to read extensively – including some schools in Indonesia. A small-scale quantitative study was carried out in second grade at one private primary school in Bandung to discover the efficacy of Reading A-Z in cultivating students' vocabulary development. Ten students with low reading performance are chosen and distributed into two groups: control & experimental. The first group is not exposed to extensive reading activities, while the latter has a 2-week reading session with various themed books from Reading A-Z. Questionnaires and Vocabulary Levels Test (VLT) by Nation & Schmitt are arranged before and after. The findings show that there is a significant improvement on the students’ vocabulary mean score of the experimental group from 49,6 to 55 while there is not any improvement shown by the control group. It is suggested that using digital literacy platform such as Reading A-Z for extensive reading program can potentially increase student’s vocabulary development.